ABOUT PROBLEMS AND METHOD OF TEACHING STUDENTS OF SENIOR CLASSES TO THE BASES OF ALGORITHMIZATION AND PROGRAMMING - Zaurbekov Н.С; Sherkhan Г.А (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Due to the high level of continuous development of science and technology, programming languages are constantly updated and changed. Programming has become an important tool for the development of creative abilities, intelligence and thinking of students, as well as the formation of knowledge, skills. The article discusses the problems of teaching the basics of programming, which allows them to organize, structure, systematize information and knowledge, understand the importance of information modeling, ways of presenting information and use it in the process of reviewing and making decisions, mastering modern information technologies . Algorithmic thinking grows throughout life under the influence of external conditions and additional factors. The need to search for new effective ways of forming algorithmic thinking in adolescents shows the connection of the importance of personality with the aim of further self-knowledge in the modern computerized world. The main purpose of this article is to identify some of the problems of teaching the basics of programming languages and ways to solve them. The study of the topic “Algorithmization and programming” revealed the importance of an effective method for the formation of algorithmic thinking in high school students in the development of algorithms and their application in solving problems.